2018
DOI: 10.3390/ijms19092739
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone Induces Cell Cycle Arrest and Apoptosis of NSCLC Cells through the PI3K/Akt/GSK-3β Pathway

Abstract: Cryptotanshinone (CTT) is a natural product and a quinoid diterpene isolated from the root of the Asian medicinal plant, Salvia miltiorrhizabunge. Notably, CTT has a variety of anti-cancer actions, including the activation of apoptosis, anti-proliferation, and reduction in angiogenesis. We further investigated the anti-cancer effects of CTT using MTS, LDH, and Annexin V assay, DAPI staining, cell cycle arrest, and Western blot analysis in NSCLC cell lines. NSCLC cells treated with CTT reduced cell growth throu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…Numerous studies have demonstrated that aberrant activation of the PI3K/Akt pathway is involved in the pathological process of bladder cancer, and its inhibition has become a useful therapy for bladder cancer [32,33]. Importantly, Kim et al demonstrated that CTT induced apoptotic cell death and cell cycle arrest through the inhibition of the PI3K/AKT/GSK3B signalling pathway in human lung cancer cells [34]. Additionally, Ke et al observed that treatment of cholangiocarcinoma cells with CTT could induce apoptosis by suppressing PI3K/AKT/NF-κB signalling pathway [35].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that aberrant activation of the PI3K/Akt pathway is involved in the pathological process of bladder cancer, and its inhibition has become a useful therapy for bladder cancer [32,33]. Importantly, Kim et al demonstrated that CTT induced apoptotic cell death and cell cycle arrest through the inhibition of the PI3K/AKT/GSK3B signalling pathway in human lung cancer cells [34]. Additionally, Ke et al observed that treatment of cholangiocarcinoma cells with CTT could induce apoptosis by suppressing PI3K/AKT/NF-κB signalling pathway [35].…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits epithelial-mesenchymal transition by modulating STAT3-chemokine (C-C motif ) ligand 2 (CCL2) pathway in human bladder cancer 5637, BFTC and T24 cells [531], and suppresses cell proliferation and migration via forkhead box protein M1 (FoxM1) downregulation in human gastric cancer SGC-7901 cells [514]. On the other hand, tanshinone I induces apoptosis via Bcl-2 down-regulation in human gastric cancer BGC-823 and SGC-7901 cells [510], while cryptotanshinone induces apoptosis through mitochondrial-, cyclin-and caspase-dependent pathways in human NSCLC A549 and NCI-H460 cells [532], as well as via ER stress in human hepatocellular carcinoma HepG2 and breast cancer MCF-7 cells [533].…”
Section: Tanshinonesmentioning
confidence: 99%
“… 2008 ; Kim et al. 2018 ). Our results demonstrated that aaptamine significantly and selectively dephosphorylated AKT and GSK3β in PI3K/AKT/GSK3β signalling cascades and concomitantly decreased cell cycle regulation drivers (CDK2/4 and Cyclin D1/E) both transcriptionally and post-transcriptionally.…”
Section: Discussionmentioning
confidence: 99%